LIMBAH LUMPUR INDUSTRI PENGOLAHAN BAJA SEBAGAI PENGGANTI PARSIAL PASIR UNTUK BAHAN BANGUNAN - Darmayasa, I Gede Oka; Widiantara, I Kadek (Jurnal Ecocentrism, 2024)
This research involves the binding/solidification of sludge waste from the steel processing industry originating from a steel industry in West Java, namely sludge waste from the waste processing process of the iron sponge production unit (direct reduction plant) and the wire rod mill production unit using cement as the binding material in the concrete mixture. The binding of sludge waste is carried out on a laboratory scale with mixture proportions of 0, 10, 20, 30, and 40% sludge waste substitution for fine aggregate/sand. Laboratory tests on the mixture include compressive strength, elastic modulus and Poisson ratio, concrete density, permeability, environmental resistance, and leaching tests with TCLP (toxicity characteristic leaching procedure). Heavy metal leaching tests for Pb, Cd, and Zn have the highest values at a 40% mixture proportion, which are 0.065 mg/ltd, 0.234 mg/lt, values below the quality standard limits for these heavy metals, which are 5.0 mg/lt, 1.0 mg/ltd, and 50 mg/lt, respectively. Environmental resistance tests indicate that the mixture has sufficient resistance after testing through 13 cycles, with the highest weight loss in the mixture sample being 13.97%, a value below the established quality standard where the maximum weight loss is 30%.